Ξ hypernuclear states predicted by next-to-leading-order chiral baryon–baryon interactions. (4th September 2021) - Kohno, M; Miyagawa, K
Abstract: The Ξ single-particle potential obtained in nuclear matter with next-to-leading-order baryon–baryon interactions in chiral effective field theory is applied to finite nuclei by an improved local-density approximation method. As a premise, phase shifts of Ξ N elastic scattering and the results of Faddeev calculations for the Ξ NN bound state problem are presented to show the properties of the Ξ N interactions in the present parametrization. First, the Ξ states in ^14 N are revisited because of recent experimental progress, including discussion on the Ξ N spin–orbit interaction that is relevant to the location of the p -state. Then the Ξ levels in ^56 Fe are calculated. In particular, the level shift which is expected to be measured experimentally in the near future is predicted. The smallness of the imaginary part of the Ξ single-particle potential is explicitly demonstrated.